2019
DOI: 10.1038/s41598-019-47920-z
|View full text |Cite
|
Sign up to set email alerts
|

Balance Impairments in Patients with Human T-Cell Lymphotropic Virus Type 1 Infection

Abstract: The human T-cell lymphotropic virus type 1 (HTLV-1) is a retrovirus from the Retroviridae family that infects cluster of differentiation 4 (CD4) T-lymphocytes and stimulates their proliferation. A severe consequence of this infection can be the HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP), which is associated with a progressive demyelinating disease of the upper motor neurons. The HAM/TSP conditions frequently present with neurological complaints such as gait impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…For Vasconcelos et al (2019) [32], the subtle balance impairment in patients without defined HAM/TSP (i.e., undetected in clinical scales) suggests that these patients may be between healthy patients and HAM/TSP and, thus, may show a risk of developing severe imbalance postural control.…”
Section: Patients Infected Withmentioning
confidence: 99%
“…OS induces demyelination and neurodegeneration instantly by lipid peroxidation, proteins, and DNA oxidation [124,125]. Many of the actors involved in this delicately adjusted network are maintained by the Keap1/Nrf2/ARE signaling pathway, a main regulator of antioxidant and phase II detoxification genes [120,121,126,127]. This pathway also has a vital role in the inflammation process and thus has significant potential in the treatment of MS [31].…”
Section: Multiple Sclerosis and Nrf2 Activationmentioning
confidence: 99%